The dispersion of Rayleigh waves in orthotropic layered half-space using matrix method - Tuan, Tran Thanh; Trung, Tran Ngoc (Vietnam Journal of Mechanics, 2016)
In this paper, the secular equation of Rayleigh surface waves propagating in an orthotropic layered half-space is derived by the matrix method.  All the layers and the half-space are assumed to have identical principle axes. The explicit form of the matrizant for each layer is obtained by the Sylvester's theorem. The derived secular equation takes only real values and depends only on the dimensionless variables and dimensionless material parameters. Hence, it is convenient in numerical calculation.